Optimalisasi Regulasi Transformasi Digital Perbankan dengan Implementasi Berbasis Environmental Social Governance Sebagai Bentuk Transisi Menuju Green Banking - Latisha, Najwa; Dirkhareshza, Rianda (Jurnal Ilmiah Penegakan Hukum, 2024)
This article aims to examine the optimization of banking digital transformation regulations in regulating digital bank risk management practices to support the transition to green banking with ESG (Environmental, Social, and Governance)-based implementation. The problem is focused on the analysis of banking digital transformation regulations. In order to approach this problem, legal theories are used as references with a normative juridical approach. The data collected through literature studies with a legislative, comparative, and conceptual approach, and analyzed qualitatively. This study concludes that in order for the green banking transition to be comprehensive, ESG-based implementation is needed, but ESG has not been regulated in a law in Indonesia. This research is important because the absence of ESG-related rules will create legal uncertainty. This can be overcome by integrating ESG-related rules in the rules of good governance principles through a law. Therefore, with the regulation of ESG-based implementation integrated in the application of good governance principles in a law, banking digital transformation regulations can be optimal in their implementation to regulate ESG-based implementation that creates legal certainty for digital banks so that the transition to green banking can be comprehensive.